Progressiveness of Islamic Economic Law in Indonesia: The Murā‘at Al-‘Ilal wa Al-Maṣāliḥ Approach - Hasanudin, Hasanudin; Mubarok, Jaih; Maulana, Muhammad Al-Fayyad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Islamic economic law is unresponsive and tends to be legal-formal in supervising Sharia finance and economic development. Economics, in fact, emphasizes the aspects of flexibility and convenience. This study aims to reveal the response of fatwas to economic and financial developments using the murā‘at al-‘ilal wa al-maṣāliḥ approach. The study use qualitative research method. The study used qualitative research methods, analyzed using the proposed fiqh and fiqh approaches. The data studied is the fatwa of the National Sharia Council (Dewan Syariah Nasional/DSN) of the Indonesian Ulema Council (Majelis Ulama Indonesia/MUI). This fatwa is examined by comparing chronologically the time, the opinion of the clergy, and economic developments. The three fatwas became the focus and debate of scholars examined to find patterns in responding to the needs of financial and economic transactions. As a result, fatwas are dynamic and responsive to industry needs. The law can change since the legal reasons (‘illat) behind it also changes. The existence of a law lies in how the cause of the law works; hence, in fatwa, there are things changing and some are permanent legal provisions. This finding has implications for corrections to previous legal provisions and changes to contracts made between financial institutions and clients.